Epoxylathyrane Derivatives as MDR-Selective Compounds for Disabling Multidrug Resistance in Cancer - Reis, Mariana Alves; Matos, Ana M.; Duarte, Noélia; Ahmed, Omar Bauomy; Ferreira, Ricardo J.; Lage, Hermann; Ferreira, Maria-José U. (Frontiers in Pharmacology, 2020)
Background Multidrug resistance (MDR) has been regarded as one of the major hurdles for the successful outcome of cancer chemotherapy. The collateral sensitivity (CS) effect is one the most auspicious anti-MDR strategies. Epoxylathyrane derivatives 1–16 were obtained by derivatization of the macrocyclic diterpene epoxyboetirane A (17), a lathyrane-type macrocyclic diterpene isolated from Euphorbia boetica. Some of these compounds were found to strongly modulate P-glycoprotein (P-gp/ABCB1) efflux. Purpose The main goal was to develop lathyrane-type macrocyclic diterpenes with improved MDR-modifying activity, by targeting more than one anti-MDR mechanism. Study design/methods In this study, the potential CS effect of compounds 1–16 was evaluated against gastric (EPG85-257), pancreatic (EPP85-181), and colon (HT-29) human cancer cells and their drug-resistant counterparts, respectively selected against mitoxantrone (EPG85-257RNOV; EPP85-181RNOV; HT-RNOV) or daunorubicin (EPG85-257RDB; EPP85-181RDB; HT-RDB). The most promising compounds (8, 15, and 16) were investigated as apoptosis inducers, using the assays annexin V/PI and active caspase-3. Results The compounds were more effective against the resistant gastric cell lines, being the CS effect more significant in EPG85-257RDB cells. Taking together the IC50 values and the CS effect, compounds 8, 15, and 16 exhibited the best results. Epoxyboetirane P (8), with the strongest MDR-selective antiproliferative activity against gastric carcinoma EPG85-257RDB cells (IC50 of 0.72 µM), being 10-fold more active against this resistant subline than in sensitive gastric carcinoma cells. The CS effect elicited by compounds 15 and 16 appeared to be by inducing apoptosis via caspase-3 activation. Structure-activity relationships of the compounds were additionally obtained through regression models to clarify the structural determinants associated to the CS effect. Conclusions This study reinforces the importance of lathyrane-type diterpenes as lead molecules for the research of MDR-modifying agents.